2003
DOI: 10.1124/jpet.103.052613
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Involvement of Supraspinal δ- and Spinal μ-Opioid Receptors in the Antihyperalgesic Effect of Chronically Administered Clomipramine in Mononeuropathic Rats

Abstract: The mechanisms of involvement of the opioidergic system in the antinociceptive effect of antidepressants remain to be elucidated. The present study was designed to determine what type of opioid receptors may be involved at the spinal and supraspinal levels in the antihyperalgesic effect of clomipramine, a tricyclic antidepressant commonly prescribed in the treatment of neuropathic pain. Its antihyperalgesic effect on mechanical hyperalgesia (paw pressure test) in rats induced by chronic constriction injury of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 32 publications
1
47
0
3
Order By: Relevance
“…Some studies have demonstrated that there is a cross-tolerance of local anesthetics with opioids, while some others believe that some other factors such as voltage-gated sodium channel effects are concerned (5,6). Notwithstanding the exemplary opioids receptors, various different receptors are influenced by opioids both in the central and the peripheral nervous system (7,8,13,14). On the other hand various studies have shown structural similarities between opioids and local anesthetic receptors in the spinal cord in some parts (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that there is a cross-tolerance of local anesthetics with opioids, while some others believe that some other factors such as voltage-gated sodium channel effects are concerned (5,6). Notwithstanding the exemplary opioids receptors, various different receptors are influenced by opioids both in the central and the peripheral nervous system (7,8,13,14). On the other hand various studies have shown structural similarities between opioids and local anesthetic receptors in the spinal cord in some parts (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The antiallodynic properties of chronic nortriptyline treatment was absent in mice deficient of ␦-opioid receptors (Benbouzid et al, 2008b), and both ␦-and -opioid receptor antagonists blocked the attenuation of neuropathic allodynia elicited by chronic TCA treatment (Benbouzid et al, 2008a). Moreover, supraspinal ␦-and spinal -opioid receptors have been proposed to be involved in the antihyperalgesic effect of chronically administered clomipramine in a mononeuropathic pain model in rats (Marchand et al, 2003). Although it is possible that these effects may result from indirect actions of TCAs on the opioidergic system (i.e., enhanced release of endogenous opioid peptides), the present data support the idea that at least a portion of the TCA analgesic effect may involve a direct agonist activity at ␦-and -opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that the antinociceptive effects of TCAs are reversed by opioid receptor antagonists (Biegon and Samuel, 1980;Gray et al, 1998;Marchand et al, 2003; Benbouzid et al, 2008a,b) and that TCAs potentiate morphine-induced analgesia both in animals (Hamon et al, 1987) and in humans (Micó et al, 2006). In animal behavioral tests predictive of antidepressant effects in humans, such as the forced swimming and learned helplessness tests, the effects of TCAs have been found to be antagonized by blockade of opioid receptors, indicating the possible participation of opioid neurotransmission in the antidepressant activity of these drugs (Devoize et al, 1982;Tejedor-Real et al, 1995;Besson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, repeated TCA (e.g., amitriptyline, nortriptyline and clomipramine) administration suppressed neuropathic pain induced by peripheral nerve injury. 26,27) However, the suppressive effects and validity periods of TCAs on VCR-induced mechanical allodynia are poorly understood. In this study, repeated administration, but not acute administration, of IMI significantly suppressed VCR-induced mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%